Optimizing Arabic Text Listening Skills through the Numbered Head Together Strategy - Mizan, Khairul; Muassomah, Muassomah; Zoni, Lapas; Alkampary, Ahmad Iqbal; Muhlis, Wachida (Arabiyatuna: Jurnal Bahasa Arab, 2024)
The study aimed to explore the application of the NHT strategy in optimizing the learning of Arabic text listening skills and to describe students' responses to its use. A lack of practice in listening results in difficulties in interacting. These difficulties are also caused by students' lack of motivation and interest, as well as a lack of vocabulary and limited understanding of sentence structure. Therefore, an alternative is needed to minimize the problem. The strategy is called Numbered Head Together (NHT). This research employed a quantitative approach with a survey method. Data were collected through observations, interviews, and questionnaires. Questionnaire data was analysed using SPSS 25. The results of the study elucidated six steps in the application of the NHT strategy: a) material preparation; b) numbering, where the teacher formed groups and assigned each group member a number from 1-5; c) listening to the text, where students were asked to listen to the text either using audio-visuals or directly from the teacher; d) asking questions, where each question given by the teacher had an identification number; e) discussion process, where students were asked to discuss the given questions; f) submission of discussion results, where students with numbers matching the question number had the responsibility to answer the question. Students' responses to the NHT strategy, measured by indicators such as interest, involvement, and perceived impact, obtained a score of 1,505 out of a maximum of 1,725, with a percentage of 87.24% (very satisfying). This research provides practical implications for improving students' learning motivation and response. Its contributions include a better understanding of the effectiveness of this strategy and providing empirical evidence for teachers to develop more effective learning strategies.